2008
DOI: 10.1007/s11274-008-9819-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of ruminant methane production: current strategies, constraints and future options

Abstract: Mitigating methane losses from cattle has economic as well as environmental benefits. The aim of this paper is to review the current approaches in relation to associated advantages and disadvantages and future options to reduce enteric methane emission from cattle. Current technologies can be broadly grouped into those that increase productivity of the animal (improved nutrition strategies) so that less methane is produced per unit of meat or milk, and those that directly modify the rumen fermentation so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 65 publications
0
51
0
5
Order By: Relevance
“…The ratio of forage to concentrate of a diet can alter the VFA profile and methane production in the rumen (Iqbal et al, 2008). Adjusting the F : C ratios is an effective means to manipulate ruminal fermentation pathways and reduce ruminal methane production due to a shift in ruminal fermentation patterns to propionate (Fahey and Berger, 1988) and a decline in the ruminal pH (VanKessel and Russell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of forage to concentrate of a diet can alter the VFA profile and methane production in the rumen (Iqbal et al, 2008). Adjusting the F : C ratios is an effective means to manipulate ruminal fermentation pathways and reduce ruminal methane production due to a shift in ruminal fermentation patterns to propionate (Fahey and Berger, 1988) and a decline in the ruminal pH (VanKessel and Russell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Methane is said to be explosive when it is present in the air in concentrations between 5-15% (Huang and He, 2008) and has a global warming potential of 21 (IPCC, 1997, Talyan et al, 2007. For the past 300 years atmospheric methane has increased by about 150% (Iqbal et al, 2008) and its atmospheric concentration has nearly tripled since preindustrial times (Houghton et al, 2001). Methane is emitted from various man-made and natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…The current method in animal husbandry is either to increase the productivity of the animal through improved nutrition in order to produce less methane per unit of meat or milk or to alter the rumen fermentation process so as to reduce the volume of methane produced (Iqbal et al, 2008). Despite all these efforts, 15% of global methane emissions come from enteric fermentation by ruminants (Houghton et al, 2001;Takahashi, 2011) gave methane emission breakdown from enteric fermentation as 12% of global, 19% of anthropogenic and 36% of agricultural while Naqvi and Sejian (2011) reported that 18% of greenhouse gas emission comes from animal husbandry.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches in the last two decades have been focused on the effects of ionophores and antibiotics on ruminal fermentation (RUSSELL, 1987). In other hand, supplement of probiotics into the rumen microorganisms, which increase propionate or butyrate and reduce the protozoa number resulted reduction in methane (IQBAL et al, 2008). But, usage of probiotics in large scale production to mitigate CH4 emissions is very expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The supplement of probiotics into the rumen microorganisms, which increase propionate or butyrate and reduce the protozoa number resulted reduction in methane emissions (IQBAL et al, 2008), but, its usage in large scale production to mitigate CH4 emissions is very expensive.…”
Section: Introductionmentioning
confidence: 99%